BAMM (BRAF Autophagy and MEK Inhibition in Melanoma): A Phase I/II Trial of Dabrafenib, Trametinib, and Hydroxychloroquine in Advanced BRAFV600-mutant Melanoma - Mehnert, Janice M; Mitchell, Tara C; Huang, Alexander C; Aleman, Tomas S; Kim, Benjamin J; Schuchter, Lynn M; Linette, Gerald P; Karakousis, Giorgos C; Mitnick, Sheryl; Giles, Lydia; Carberry, Mary; Frey, Noelle; et al. (Clinical cancer research, 2022)
Autophagy is a resistance mechanism to BRAF/MEK inhibition in BRAFV600-mutant melanoma. Here we used hydroxychloroquine (HCQ) to inhibit autophagy in combination with dabrafenib 150 mg twice daily and trametinib 2 mg every day (D+T). We conducted a phase I/II clinical trial in four centers of HCQ + D+T in patients with advanced BRAFV600-mutant melanoma. The primary objectives were the recommended phase II dose (RP2D) and the one-year progression-free survival (PFS) rate of >53%. Thirty-four patients were evaluable for one-year PFS rate. Patient demographics were as follows: elevated lactate dehydrogenase: 47%; stage IV M1c/M1d: 52%; prior immunotherapy: 50%. In phase I, there was no dose-limiting toxicity. HCQ 600 mg orally twice daily with D+T was the RP2D. The one-year PFS rate was 48.2% [95% confidence interval (CI), 31.0%-65.5%], median PFS was 11.2 months (95% CI, 5.4-16.9 months), and response rate (RR) was 85% (95% CI, 64%-95%). The complete RR was 41% and median overall survival (OS) was 26.5 months. In a patient with elevated LDH (n = 16), the RR was 88% and median PFS and OS were 7.3 and 22 months, respectively. HCQ + D+T was well tolerated and produced a high RR but did not meet criteria for success for the one-year PFS rate. There was a high proportion of patients with pretreated and elevated LDH, an increasingly common demographic in patients receiving targeted therapy. In this difficult-to-treat population, the RR and PFS were encouraging. A randomized trial of D+T + HCQ or placebo in patients with BRAFV600-mutant melanoma with elevated LDH and previous immunotherapy is being conducted.